Gynecologic-Oncology Team-Based Learning Session for Third-Year Ob/GYN Medical Student Clerkship - Katrina Davis (Association of American Medical Colleges, 2007)
Abstract This team-based learning resource is designed to supplement third-year medical student clerkships in obstetrics and gynecology. This session addresses primary objectives listed by the Association of Professors of Gynecology and Obstetrics Medical Student Educational Objectives (8th edition) and is geared to prepare students for gynecologic-oncology questions that will be encountered on medical licensure exams. This resource strictly adheres to team-based learning guidelines. As such, student first prepare for the session ahead of time by reading from an assigned textbook. Students then complete the included readiness assurance test first individually, and then again as part of a group. This is followed by the completion of application exercises aimed at the utilization of knowledge accumulated in preparation for the readiness exams.